ANALISIS KONSISTENSI PELAKSANAAN SHOLAT DALAM MEMBENTUK KETENANGAN JIWA MAHASISWA FAI UMB KELAS A0 - Nurfana Salam; La Jusu; Madi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The urgency of this study lies in the correlation between the consistency of performing (prayer) and the level of inner peace. Thisiresearch aims toiexamine the extentiito whichiiconsistency in performing prayer influences students’ emotional stability and psychological calmness. iThe study wasiconducted onistudents of the Faculty of Islamic Studies (FAI), with a population and sample consisting of four classes totaling 28 students. Thisiiresearch employs aiiidescriptive qualitative approach, iwith theiiiresearcher as theiiimain instrument toiiiunderstand how consistencyiiin performing prayer shapes students’ inner peace in FAI UMB Class A0. iDataiwere collectedithrough interviews, iobservations, iand documentation, iand analyzedithrough dataireduction, idata display, iayanand conclusion drawing. iThe results indicateithat there is a significant and positive relationship between the consistency of performing prayer and the level of inner peace. The findings show that students who consistently perform prayers on time and in accordance with Islamic teachings tend to have more stable psychological conditions and greater emotional calmness. The results also suggest that prayer plays a substantial role in reducing students’ anxiety, while the remaining influence is affected by other external factors.